Insights concerning how students view the impact of technology in lifelong learning - Nikoçeviq-Kurti, Elmedina (Teorija in praksa, 2025)
Technology has transformed education into a lifelong journey on which learners’ knowledge and adaptability is vital. Embracing technology enables learners to navigate a world of information, fostering continuous exploration and growth. This qualitative case study analyses reflective essays to explore the experiences of 15 Kosovo university students with technology in the context of lifelong learning. In addition, seven students were interviewed to gather more in-depth insights. Thematic analysis of the data revealed several key findings, including the influence of technology on approaches to lifelong learning, the challenges faced while using technology for learning, the skills and knowledge acquired through technology, differences in technology use among peers, and the future evolution of technology. Overall, the study helps to better understand how technology shapes lifelong learning and the implications it holds for the professional development of university students.
Keywords: lifelong learning; Permanentno izobraževanje; reflection; refleksija; Študenti; technology; Tehnologija; vseživljenjsko učenje